Effect of Concept Mapping in Teachng of Physics in Senior Secondary Schools in Portharcourt Local Government Area Rivers State - Doris, Omeodu M. (European Scientific Journal, ESJ, 2018)
The study examined the effect of concept mapping in the teaching of physic in senior secondary school in port Harcourt local government area Rivers state. The purpose of the study was to determine the effect of concept mapping on the teaching of physics. The study also found the difference in the academic achievement of students taught physics with concept mapping and conventional teaching method. Eighty-four SS3 physics students were used for the study. Forty-three 43 comprised of the experimental group and fortyone in the control group. The study adopted pre-test post test quasi experimental design. The instrument used for the study was Physics achievement test (PAT).The instrument contained 25 multiple choice questions, in which each of the questions 2 marks. The instrument was validated by two experts in the department of science education in Rivers State University. Pearson product moment correlation coefficient was used to ascertain the instrument’s level of reliability, which resulted to r value of 0.62. findings of the study shows that students taught Physics with concept mapping significantly better than those taught with conventional method. Also the study found that there was no significant difference between male and female students taught Physics with concept mapping. The study recommended that teachers should imbibe concept mapping method in the teaching of Physics so as to enhance students’ comprehension, identification of relationships that exits between concepts and creativity.